Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/app.11037
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of terpolymers having a phospholipid polar group and poly(oxyethylene) in the side chain and their protein adsorption–resistance properties

Abstract: Terpolymers having phospholipid polar groups were synthesized from 2-methacryloyloxyethyl phosphorylcholine (MPC), methacryloyl or acryloyl poly(oxyethylene) macromonomers (POEM) [(CH 2 CH 2 O) n (where n ϭ 2-23); PEOM(2), PEOM(23), ME(9), Ph(6)], and n-butyl methacrylate (BMA). The characteristics of these terpolymer membranes were investigated by water content (H) and X-ray photoelectron spectroscopy. The content of water in the terpolymer increased with increasing content of MPC and length of oxyethylene un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The adsorption experiments were performed by BCA protein assay reagent. [30][31][32] Polymer-modied silicon wafers with 1 cm  1 cm area were immersed in PBS solution containing 2 mg mL À1 BSA or 1 mg mL À1 Fg. The adsorption was incubated in shaker at a constant temperature of 37 C for 24 h. Aer adsorption, the samples were taken out and rinsed with PBS three times to remove the non-adsorbed protein.…”
Section: Protein Adsorptionmentioning
confidence: 99%
“…The adsorption experiments were performed by BCA protein assay reagent. [30][31][32] Polymer-modied silicon wafers with 1 cm  1 cm area were immersed in PBS solution containing 2 mg mL À1 BSA or 1 mg mL À1 Fg. The adsorption was incubated in shaker at a constant temperature of 37 C for 24 h. Aer adsorption, the samples were taken out and rinsed with PBS three times to remove the non-adsorbed protein.…”
Section: Protein Adsorptionmentioning
confidence: 99%
“…Ishihara and Nakayama groups had prepared a se rial of MPC modified polymers to improve their bio compatibility and hemocompartibility [14,15]. Oishi et al also reported that the polymers bearing a phos phorylcholine moiety had the excellent antithrombo genicity [16]. However, some of these materials showed poor mechanical properties and the limitation on the applications as blood contacting materials.…”
Section: Introductionmentioning
confidence: 98%
“…One direct and effective way is the modification of the surface with protein‐resistant materials 3. Various polymer materials, such as heparin,8 dextran,9 polyoxazolines,10 poly(ethylene glycol) (PEG) or oligo(ethylene glycol),11, 12 and zwitterionic polymers,13–16 have been used to physically modify the surface. Particularly, PEG‐based materials with excellent nonfouling capabilities and biocompatibility have been used widely 17, 18.…”
Section: Introductionmentioning
confidence: 99%